Benefits of Stroke Treatment Using a Mobile Stroke Unit Compared With Standard Management: The BEST-MSU Study Run-In Phase. Issue 12 (December 2015) - Bowry, Ritvij; Parker, Stephanie; Rajan, Suja S.; Yamal, Jose-Miguel; Wu, Tzu-Ching; Richardson, Laura; Noser, Elizabeth; Persse, David; Jackson, Kamilah; Grotta, James C.
Abstract : Background and Purpose—: Faster treatment with intravenous tissue-type plasminogen activator (tPA) is likely to improve outcomes. Optimizing prehospital triage by mobile stroke units (MSUs) may speed treatment times. The Benefits of Stroke Treatment Delivered Using a Mobile Stroke Unit (BEST-MSU) study was launched in May 2014 using the first MSU in the United States to compare stroke management using an MSU versus standard management (SM). Herein, we describe the results of the prespecified, nonrandomized run-in phase designed to obtain preliminary data on study logistics. Methods—: The run-in phase consisted of 8 MSU weeks when all-patient care occurred on the MSU and 2 SM weeks when the MSU nurse met personnel on scene or at the emergency department to ensure comparability with MSU patients. Telemedicine was independently performed in 9 MSU cases. Results—: Of 130 alerts, 24 MSU and 2 SM patients were enrolled. Twelve of 24 MSU patients received tPA on board; 4 were treated within 60 minutes of last seen normal, and 4 went on to endovascular treatment. There were no hemorrhagic complications. Four had primary intracerebral hemorrhage. Agreement on tPA eligibility between the onsite and telemedicine physician was 90%. Conclusions—: The run-in phase provided a tPA treatment rate of 1.5 patients per week, assured us that treatment within 60 minutes of onset is possible, and enabled enrollment of patients on SM weeks. We also recognized the opportunity to assess the effect of the MSU on endovascular treatment and intracerebral hemorrhage. Challenges include the need to control biased patient selection on MSU versus SM weeks and establish inter-rater agreement for tPA treatment using telemedicine.